2021
DOI: 10.21203/rs.3.rs-500633/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stromal cell-derived factor 1 secreted by cancer-associated fibroblasts promotes lncRNA Xist through CXCR4 and facilitates invasion and metastasis of non-small cell lung cancer

Abstract: Cancer-associated fibroblasts (CAFs) abundantly exist in NSCLCs and promote tumor progression in most solid tumors. This study investigated the effect of CAFs on NSCLC. CAFs and normal fibroblasts (NFs) were isolated and identified. CAFs or NFs were cocultured with NSCLCs cells. Cell invasion and migration, and expression of E-cadherin, N-cadherin, SDF-1, CXCR4 and Xist were measured. SDF-1/CXCR4 axis inhibitor ADM3100 or low expression of Xist was added to verify the invasion and metastasis of NSCLC. The bind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…As in the case of MSCs, the influence of CAFs on the SDF-1/CXCR4 signalling pathway has recently been extensively studied. Recent studies show a significant influence of CAFs on this pathway, which interplay to among others, invasiveness and metastasis of NSCLC or progression of endometrial cancer [42,43]. Wang et al already in 2008, indicated that this pathway may be a promising therapeutic target, in their research they showed that the overall survival time of patients with positive CXCR4 in pancreatic cancer was lower than that of patients without this marker [44].…”
Section: Cancer-associated Fibroblasts In Tmementioning
confidence: 99%
“…As in the case of MSCs, the influence of CAFs on the SDF-1/CXCR4 signalling pathway has recently been extensively studied. Recent studies show a significant influence of CAFs on this pathway, which interplay to among others, invasiveness and metastasis of NSCLC or progression of endometrial cancer [42,43]. Wang et al already in 2008, indicated that this pathway may be a promising therapeutic target, in their research they showed that the overall survival time of patients with positive CXCR4 in pancreatic cancer was lower than that of patients without this marker [44].…”
Section: Cancer-associated Fibroblasts In Tmementioning
confidence: 99%